The Relationship Between Job Statification And Health Workers Performane At Ende Regional Public Hospital - Mohammad Risyan Karnain; Pipit Festi Wiliyanarti (Global Journal of Health Administration, 2025)
Objective: To identify how healthcare worker performance directly impacts the quality of hospital services and patient outcomes, this study examines the link between job satisfaction and staff performance at RSUD Ende, East Nusa Tenggara, Indonesia. In regions like Ende, healthcare facilities face challenges such as high workloads, insufficient resources, and limited access to professional development, which can negatively affect employee morale, retention, and service quality. According to the Indonesian Audit Board (BPK, 2024), RSUD Ende demonstrates weak planning and monitoring in inpatient services, indicating a need for stronger human resource strategies. While previous studies have explored job satisfaction and performance, few have focused on remote, resource-limited hospitals, particularly in Eastern Indonesia. This study aims to fill that gap by analyzing the impact of job satisfaction on healthcare worker performance to guide hospital leadership and policymakers in creating targeted interventions. Method: This article used a descriptive research design with a cross-sectional approach. The study involved a randomly selected sample of 100 employees from RSUD Ende. Data were collected using a structured questionnaire with Likert scale items and analyzed using the Chi-Square non-parametric test. Results: The majority of respondents were female (70%), aged 30–40 years, married (80%), and held a Diploma III degree (70%). Most had 5–10 years of work experience. Overall, job satisfaction levels were rated as “moderately satisfied,” while healthcare worker performance in outpatient care was considered “fairly good.” The findings suggest a significant relationship between job satisfaction and staff performance in a limited-resource hospital setting.